Phytochrome in Cultured Wild Carrot Tissue: II. Dark Transformations - Wetherell, Donald F. (1970)
Disappearance and transformation of phytochrome in light-treated, dark-grown cultured tissue of wild carrot (Daucus carota L.) have been analyzed. Evidence is presented for the existence of two populations of far red-absorbing phytochromes: one which is subject to reversion, and a second which undergoes loss of photoreversibility. Phytochrome levels and transformation characteristics have been compared for several strains and developmental stages of cultured wild carrot tissue.